Assessment of Causes of Wounds Infection (WI) after Caesarean Section at Al - Batol Teaching Hospital in Iraq - Nooralhuda Salh; Salwa Turki (Kufa Journal for Nursing Sciences)
Objectives:  the study aimed to identify the causes of wound infection occurrence of post cesarean section and to find out the relationship between causes and some socio-demographic data.